Problem niemiecki w okresie panowania „Ducha Genewy” - Bartczak, Aneta (Acta Universitatis Lodziensis. Folia Historica, 2009)
After signing the Act of Unconditional Capitulation, and ending the Second World War in Europe, Germany was divided into four occupation zones, whereas Berlin was splitted into four sectors. The control and responsibility for zones and sectors were bom upon the USA, the USSR, the Great Britain and France, due to the acts signed within the years: 1944 and 1945. The acts were to make a decision about the future concerning four countries enumerated above. Dispersion o f the common politics of four superpowers towards “Germany and Great Berlin as the integrity” caused the actual setting of two German countries in 1949, namely the Republic of Federal Germany and German Democratic Republic, closely connected witch the political - military blocks, that is NATO (North Atlantic Treaty Organization) and The Warsaw Pact (Alliance of Communist Nations) since 1955. From that time the Gentian issue has become the core element of reality. In the first half of 1950s the previous suspense connected with the German issue was inferior to difficult dialogue between the East and the West initiated in Geneva (from 18th July until 23rd July 1955) during the conference of political leaders of four superpowers, specified as “the ghost of Geneva”. The antagonistic blocks of the countries, being aware of danger of the new war outbreak, to with the politics of power would uneritably lead, started the period of transient cooperation. The period was characterized with attempts to develop the new rules of safety and disarmament. The German issue stepped down to the background, in comparison to the previous years, being the core point of the superpowers interest any more. Germany started to be viewed and treated as the element of militant balance to witch the countries on the oid continent were striving for after determining the political influences. As it turned out, the real prospects of achieving the detente and normalization of relations between the East and West were faint. First of all, a state of affairs resulted from the irreconcilable position taken by the sides of the dialogue as far as the above mentioned issues and concerned. The natural consequence was the impossibility of solving the German case, that is creating the premise enabling the unification of the nation being tom between two countries. Not only was the pan - German politics (the Deutschlandpolitic) absorbing the Republic of Federal Germany and German Democratic Republic, but also constituted the essential element of international politics, that is was its function. Taking into consideration the period in this facet, one should view it as time assigned for regeneiation of strength, modification of strategy and political tactics as well as military structure inside the blocks, in a word - for “taking a deep breath before the next confrontation which was initiated by USSR being disappointed with ineffectiveness ot diplomatic endeavours taken up so for. Thanks to the USSR, the centre of political gravity was transmitted again from macro- to micro-scale on more and more urgent Berlin ground, tipping the balance and being the barometer of moods and relationships prevailing between four superpowers and two German countries.